GATEKEEPER RELOAD: the expansion of news planning in the age of artificial intelligence, applied development, and conceptual reconfiguration model - Piccinin, Fabiana; Paulino, Rita; Carneiro dos Santos, Marcio (Brazilian journalism research, 2026)
ABSTRACT – Artificial intelligence is reshaping journalism and concepts associated with gatekeeping theories and newsworthiness criteria. This article reflects on changes in the initial stage of news production—the conception and scripting of stories—through human-machine collaboration resulting from the use of virtual assistants in editorial planning. Based on applied research, using Design Science Research Methodology (DSRM) instantiations to create an artifact that connects theory to emerging practices, this paper presents an experiment with a virtual assistant model, showing its levels of control and interference as well as its impact on news selection and planning. The results indicate possibilities for efficiency and innovation, and ethical and operational implications for editorial autonomy. RESUMO – A inteligência artificial vem reconfigurando o jornalismo e conceitos associados às teorias do gatekeeping e dos critérios de noticiabilidade. O artigo reflete sobre as mudanças na etapa inicial da produção jornalística – concepção e roteirização da pauta – mediante a colaboração humano-máquina advinda do uso de assistentes virtuais no planejamento editorial. A partir da pesquisa aplicada, com base nas instanciações da Design Science Research Methodology (DSRM), na concretização de um artefato que conecta a teoria às práticas emergentes, o artigo apresenta uma experiência com um modelo de assistente virtual, mostrando seus níveis de controle e interferência e seu impacto na seleção de pautas e planejamento jornalístico. Os resultados indicam possibilidades de eficiência e inovação, mas também implicações éticas e operacionais na autonomia editorial. RESUMEN – La inteligencia artificial está reconfigurando el periodismo y los conceptos asociados a las teorías del gatekeeping y los criterios de noticiabilidad. El artículo reflexiona sobre los cambios en la etapa inicial de la producción periodística – concepción y guionización de la agenda – mediante la colaboración entre humanos y máquinas derivada del uso de asistentes virtuales en la planificación editorial. A partir de la investigación aplicada, basada en las Instancias de la Metodología de Investigación en Ciencia del Diseño (DSRM) en la realización de un artefacto, que conecta la teoría con las prácticas emergentes, se presenta una experiencia con un modelo de asistente virtual, mostrando sus niveles de control e interferencia y el impacto en la selección y planificación periodística. Los resultados indican posibilidades de eficiencia e innovación, así como implicaciones éticas y operativas en la autonomía editorial.